Quick Design Methods for characterization of Used Lubricating Oils - Loayza P., Jorge (2005)
The used lubricating oils are wastes of post consumption that require an integral management, for which is necessary that the operators have a set of simple, fast, economic and reliable methods that allow them to characterize oils used for their later advantage. The methods that appear are: water content, (in qualitative form and quantitative form), density and determination of the state of additives (dispersing) or «spot test».